Securitization and the limits of democratic security (2015)
From independence in the 19th century until the 1980s, when a wave of democracy took hold in much of Latin America and violent armed conflict in Central America was nearing an end, security thinking and policy was almost exclusively the domain of the military. During the Cold War in particular, the leading mode of thought, national security doctrine (NSD), legitimated authoritarian rule and widespread repression of leftist dissent, based upon the idea that domestic ‘Communist’ movements constituted the region’s largest security threat. For the last 30 years, however, Latin American scholars and practitioners have challenged traditional, militarized readings of security, and developed new and alternative conceptions following democratization.